2003
DOI: 10.1074/jbc.m212766200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-dependent Regulation of Kv2.1 Channel Activity at Tyrosine 124 by Src and by Protein-tyrosine Phosphatase ε

Abstract: Voltage-gated potassium (Kv) channels are a complex and heterogeneous family of proteins that play major roles in brain and cardiac excitability. Although Kv channels are activated by changes in cell membrane potential, tyrosine phosphorylation of channel subunits can modulate the extent of channel activation by depolarization. We have previously shown that dephosphorylation of Kv2.1 by the nonreceptor-type tyrosine phosphatase PTP⑀ (cyt-PTP⑀) down-regulates channel activity and counters its phosphorylation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 50 publications
4
63
0
Order By: Relevance
“…The authors suggested that the difference compared with results of K v 2.1 in a heterologous expression system could be due to the interaction of K v 2.1 with silent K v subunits or to a different phosphorylation state of K v 2.1 in cultured neurons compared with heterologous expression. The degree of phosphorylation influences the voltage dependent properties of K v 2.1, and different degrees of K v 2.1 phosphorylation have been reported in different cells (15,17,18,21,35). To exclude the hypothesis that differentially phosphorylated K v 2.1 channels caused the two components of the inactivation curve, we investigated the effect of dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the difference compared with results of K v 2.1 in a heterologous expression system could be due to the interaction of K v 2.1 with silent K v subunits or to a different phosphorylation state of K v 2.1 in cultured neurons compared with heterologous expression. The degree of phosphorylation influences the voltage dependent properties of K v 2.1, and different degrees of K v 2.1 phosphorylation have been reported in different cells (15,17,18,21,35). To exclude the hypothesis that differentially phosphorylated K v 2.1 channels caused the two components of the inactivation curve, we investigated the effect of dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…cyt-PTPe dephosphorylates Kv2.1 predominantly at Y124, thereby down-regulating channel activity and countering phosphorylation of this residue by c-Src. RPTPe can dephosphorylate Kv2.1 as well (Peretz et al, 2000;Tiran et al, 2003). We, therefore, expressed Kv2.1 in the presence of Y527F Src, which cannot be activated by RPTPe, to ensure channel phosphorylation.…”
Section: Neu Activates C-src Via Rptpe Phosphorylation D Berman-golanmentioning
confidence: 99%
“…It has been established that this type of regulation involves the production of cAMP and subsequent phosphorylation by protein kinase A (PKA). Tyrosine kinases have also been reported to modulate the activity of cardiac ion channels (Shuba & McDonald, 1997;Zhou et al, 1997;Wang & Lipsius, 1998;Hool et al, 1998;Maier et al, 1999;Mason et al, 2002;Tiran et al, 2003). We previously demonstrated that genistein, a tyrosine kinase inhibitor, can increase the sensitivity of cardiac ion channels to b 1 -AR stimulation, suggesting that basal tyrosine kinase activity inhibits badrenergic responsiveness in cardiac myocytes (Hool et al, 1998).…”
Section: Introductionmentioning
confidence: 99%